2014
DOI: 10.3109/14397595.2014.927969
|View full text |Cite
|
Sign up to set email alerts
|

Efficient diagnosis of Sjögren's syndrome to reduce the burden on patients

Abstract: These results suggest that the following diagnostic procedure for Sjögren's syndrome would reduce burden on patients. When clinicians choose examination items for diagnosing Sjögren's syndrome, they should first select which criteria to use. Then, to minimize the number of examination items, examinations should be performed in order of anti-SSA antibody, lip biopsy, and parotid gland sialography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In this study, the high specificity was found in 2002 AECG criteria (92.19%) and 2012 ACR criteria (95.31%) to classify SS patients, however, the unsatisfactory sensitivity was also showed for 2002 AECG criteria (53.69%) and 2012 ACR criteria (59.06%). Similar results can be in other studies [ 2 , 10 , 11 , 17 ]. The new point-scoring diagnostic system was able to significantly improve the sensitivity for the diagnosis of SS while maintain a high specificity ( Table 4 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the high specificity was found in 2002 AECG criteria (92.19%) and 2012 ACR criteria (95.31%) to classify SS patients, however, the unsatisfactory sensitivity was also showed for 2002 AECG criteria (53.69%) and 2012 ACR criteria (59.06%). Similar results can be in other studies [ 2 , 10 , 11 , 17 ]. The new point-scoring diagnostic system was able to significantly improve the sensitivity for the diagnosis of SS while maintain a high specificity ( Table 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 41.31% patients with suspicious SS had not performed minor salivary glands biopsy. A qualitative SSG was mentioned in the 2002 AECG criteria, but it has been complained of low specificity and radiation exposure although it has high sensitivity [ 2 , 4 , 11 , 17 ]. In fact, radionuclide imaging of salivary gland yield only relatively low effective radiation doses compared with computed tomography (CT) for sialography [ 19 , 20 , 21 , 22 ], and has been increasingly accepted by clinicians and patients for it is noninvasive, convenient, and reasonably priced.…”
Section: Discussionmentioning
confidence: 99%
“…As SS-specific biomarkers are unavailable to date, SS diagnosis requires the measurement of multiple clinical parameters, including less invasive blood tests to invasive MSGBx (25). The pathological role of anti-Ro/SSA in hyposalivation is unclear, although its association with extraglandular manifestations is relatively well accepted (6,26).…”
Section: Discussionmentioning
confidence: 99%